Lead-based high-power piezoelectric ceramic and water-based tape casting method for preparing the same

CN122977841APending Publication Date: 2026-10-27XI AN JIAOTONG UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611246190.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-17
Publication Date
2026-10-27

AI Technical Summary

Benefits of technology

本发明提供了一种适用于高性能铅基大功率压电陶瓷的水基流延成型工艺,该方法解决了现有水基流延技术主要局限于KNN等无铅压电陶瓷体系、难以满足铅基大功率压电陶瓷对高机械品质因数(Qm)、高振动速度(Vm)以及稳定机电性能要求的问题。同时,针对铅基大功率压电陶瓷在水基加工过程中存在的粉体化学稳定性不足、离子溶出导致组分偏移、浆料分散及流变性能难以调控以及生坯力学性能不足等关键技术问题,本发明实现了铅基大功率压电陶瓷的稳定化水基流延制备。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122977841A_ABST
    Figure CN122977841A_ABST
Patent Text Reader

Abstract

The application discloses a lead-based high-power piezoelectric ceramic and a water-based tape casting preparation method thereof, and belongs to the technical field of lead-based piezoelectric ceramics. The method comprises the following steps: adding PMnN-PYN-PZT powder into an aqueous solution containing a dispersant AKM-0531, uniformly dispersing, and adjusting pH; then adding a binder PVA, a plasticizer PEG and a defoaming agent 204, and mixing to obtain a slurry; and through casting film forming, drying, lamination, warm isostatic pressing, glue removal and sintering, a multilayer high-power piezoelectric ceramic is obtained. The high-performance high-power piezoelectric ceramic with a compact structure and no impurity phase is prepared, and the following advantages are realized d 33 >280、 Q m >1200、The index that the vibration speed is greater than 2.0 m / s provides a feasible technical path for the water-based preparation of the lead-based high-power piezoelectric ceramic.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lead-based piezoelectric ceramics technology, specifically relating to a lead-based high-power piezoelectric ceramic and its water-based casting molding preparation method. Background Technology

[0002] Piezoelectric ceramics are a class of functional materials capable of converting mechanical energy into electrical energy, and are widely used in sensors, actuators, and high-power transducers. Based on their material properties, piezoelectric ceramics are generally classified into two categories: "soft" piezoelectric ceramics and "hard" piezoelectric ceramics. Soft piezoelectric ceramics, in particular, possess a higher piezoelectric constant (…). d 33 High-performance piezoelectric ceramics, with their high dielectric constant and strong electrostrictive response, are mainly used in low-power electronic devices such as sensors and filters. Hard piezoelectric ceramics, on the other hand, are primarily used in high-power electronic devices, requiring a high mechanical quality factor (…). Q m Piezoelectric ceramics possess comprehensive properties such as low dielectric loss, high mechanical strength, and high vibration velocity to meet high-power, high-reliability operating conditions. However, there are often significant interrelationships among the key performance parameters of piezoelectric ceramics. Typically, improving... d 33 It is necessary to enhance domain wall mobility, but stronger domain wall activity leads to increased mechanical losses. Q m Decrease; conversely, increase by restricting domain wall movement. Q m It will also reduce the material cost d 33 Therefore, high-power piezoelectric ceramics need to have excellent piezoelectric properties, Q m Achieving a reasonable balance between material loss and performance optimization increases the difficulty of material preparation.

[0003] In terms of fabrication technology, tape casting is the mainstream process for achieving thick films and multilayer structures of piezoelectric ceramics. Depending on the dispersion medium, tape casting processes can be divided into organic tape casting and water-based tape casting. While traditional organic tape casting technology is relatively mature, the organic solvents used have problems such as volatile organic compound (VOC) emissions, flammability, and high wastewater treatment costs. In contrast, water-based tape casting uses water as the dispersion medium, offering advantages such as high processing safety and lower environmental impact, and is gradually gaining attention in the field of functional ceramic forming. The existing patent CN121779114A, "A Water-Based Tape Casting Method for Lead-Free Piezoelectric Ceramic Thin Films," reports the water-based tape casting preparation of lead-free systems (such as KNN-based) piezoelectric ceramic thin films, and has obtained scores higher than 200. d 33 However, this method mainly targets high-voltage electrically responsive lead-free piezoelectric ceramic systems and does not address high-voltage...Q m The performance requirements of high-power ceramics mean they cannot be directly applied to rigid systems.

[0004] Meanwhile, for lead-based piezoelectric ceramics, water-based processing also faces unique challenges in terms of powder chemical stability: lead ions are prone to dissolution in water, leading to powder stoichiometry deviation and defect formation, which in turn affects the slurry dispersion behavior and the final microstructure and electrical properties of the ceramic; in addition, the rheological behavior of water-based slurries is highly sensitive to pH value and the type of organic additives. If not properly controlled, it is difficult to obtain a stable slurry suitable for casting and film formation, and the strength, flexibility and lamination bonding of the green body are often lower than those of the organic system, increasing the risk of defects in the debinding and sintering processes.

[0005] In summary, the water-based casting process for lead-based high-power piezoelectric ceramics needs to address the inherent properties of the material. d 33 and Q m In addition to performance contradictions, it is also necessary to solve process problems such as powder stability and slurry formability in water-based processing environments. Summary of the Invention

[0006] To overcome the shortcomings of the prior art, the present invention aims to provide a lead-based high-power piezoelectric ceramic and its water-based casting molding preparation method. This method involves controlling the pH value of the slurry to a suitable range to inhibit lead leaching, optimizing the ratio of dispersant and organic additives (PVA, PEG, etc.) to obtain a slurry with stable dispersion and shear-thinning properties, and combining this with a warm isostatic pressing, segmented debinding, and oxygen atmosphere sintering regime that matches the characteristics of water-based green bodies. Ultimately, this method produces a high-performance, high-power piezoelectric ceramic with a dense structure and no impurity phases. d 33 >280、 Q m The parameters >1200 and vibration velocity greater than 2.0 m / s provide a feasible technical path for the water-based preparation of lead-based high-power piezoelectric ceramics.

[0007] To achieve the above objectives, the present invention employs the following technical solution: This invention provides a water-based casting method for preparing lead-based high-power piezoelectric ceramics, comprising the following steps: Step 1, high-power piezoelectric ceramic powder 0.06Pb(Mn) 1 / 3 Nb 2 / 3 O3-0.04Pb(Yb) 1 / 2 Nb 1 / 2PbTiO3-0.42PbTiO3-0.48PbZrO3 (PMnN-PYN-PZT) is added to an aqueous solution containing a dispersant. Through mixing and degassing, the ceramic powder is fully wetted and uniformly dispersed to form a stable suspension. The dispersant is a polyether-based dispersant, AKM-0531, and its concentration is 0.2~1.2 wt% of the ceramic powder. Step 2: Add acid-base adjusters acetic acid and / or ammonia to the homogeneous suspension to adjust the pH value of the suspension to 8-10; Step 3: Add binder, plasticizer, and defoamer to the suspension obtained in Step 3 and mix thoroughly using a mixing defoamer. The binder is water-soluble polyvinyl alcohol (PVA), the plasticizer is polyethylene glycol (PEG), and the defoamer is Aladdin's defoamer 204. The binder accounts for 4-7 wt% of the ceramic powder mass, the plasticizer accounts for 0.75-3 wt% of the ceramic powder mass, and the defoamer accounts for 1.3 wt% of the ceramic powder mass. Preferably, the amount of polyvinyl alcohol added is 6 wt% of the lead-based high-power piezoelectric ceramic powder mass, and the amount of polyethylene glycol added is 1 wt% of the lead-based high-power piezoelectric ceramic powder mass. Step 4: Cast the slurry obtained in Step 3 into a film in a casting machine; Step 5: Dry, stack, and isostatically press the cast film obtained in Step 4 to obtain the cast film preform; Step 6: Remove the binder and sinter the cast film preform obtained in Step 5 to obtain a multilayer high-power piezoelectric ceramic.

[0008] The mixing speed in step 1 is 1800 r / min, and the time is 4 min; the ceramic powder has an average particle size of 200~300 nm.

[0009] The mixing speed in step 3 is 1800 r / min, and the time is 10~15 min.

[0010] In step 4, the height of the casting doctor blade is 200~250 μm, the casting rate is 0.15~0.20 m / min, the drying temperature is 40~70 ℃, and the thickness of the resulting cast film is 20~30 μm.

[0011] The isostatic pressing process described in step 5 includes: preheating at 75 °C for 120 min, holding at 10 MPa for 2 min, holding at 25 MPa for 2 min, and holding at 40 MPa for 2 min.

[0012] In step 6, the temperature range for debinding is 30~400 ℃, the heating rate is 0.1~0.5 ℃ / min, and the holding time is 120 min; the sintering atmosphere is O2, and the sintering is carried out at 1150 ℃ for 240 min.

[0013] The present invention also provides a lead-based high-power piezoelectric ceramic prepared by the method described above, wherein the piezoelectric constant of the lead-based high-power piezoelectric ceramic is... d 33 ≥287, Mechanical Quality Factor Q m ≥ 1200, vibration velocity V m ≥ 2.0 m / s.

[0014] Compared with the prior art, the present invention has the following beneficial effects: This invention provides a water-based casting process suitable for high-performance lead-based high-power piezoelectric ceramics. This method solves the problem that existing water-based casting technologies are mainly limited to lead-free piezoelectric ceramic systems such as KNN, and are difficult to meet the high mechanical quality factor requirements of lead-based high-power piezoelectric ceramics. Q m ), high vibration velocity ( V m This invention addresses the issues of insufficient chemical stability of lead-based high-power piezoelectric ceramics during water-based processing, including component shift due to ion dissolution, difficulty in controlling slurry dispersion and rheological properties, and insufficient mechanical properties of green bodies. It also realizes the stable water-based casting preparation of lead-based high-power piezoelectric ceramics.

[0015] This invention optimizes the dispersion stability of ceramic powder, the rheological properties of the slurry, and the mechanical properties of thick films by systematically controlling the pH value, dispersant content, polyvinyl alcohol (PVA) binder, and polyethylene glycol (PEG) plasticizer content of the slurry. Inductively coupled plasma analysis and Zeta potential testing clarified the influence of the slurry environment on ion leaching behavior and particle dispersion stability during water-based processing. Optimizing the slurry pH value effectively reduced ion dissolution of lead-based piezoelectric ceramic powder in aqueous media. When pH=10, the Pb content in the suspension... 2+ The leaching amount decreased significantly from 6.44 wt% under pH=2 conditions to 10 wt%. -4 The wt% concentration of the slurry was reduced, and the absolute value of the zeta potential of the suspension reached approximately 40 mV, indicating that the optimized slurry system has good dispersion stability.

[0016] Based on this, the present invention further optimizes the casting slurry formulation, obtaining an optimal slurry system with a dispersant content of 0.6 wt%, a PVA content of 6 wt%, a PEG content of 1 wt%, and a defoamer content of 1.3 wt%. This slurry exhibits good dispersion stability and suitable shear thinning characteristics, solving the problems of viscosity fluctuation, insufficient flow performance, and insufficient ceramic thick film strength in traditional water-based casting processes. The ceramic green body prepared using this slurry has high mechanical properties, with a tensile strength of approximately 3.3 MPa and a fracture strain of approximately 18%, which can meet the requirements of subsequent lamination, cutting, and other processing steps for the structural integrity of the green body.

[0017] The PMnN-PYN-PZT multilayer high-power piezoelectric ceramic prepared by the method of this invention has a uniform and dense microstructure, which can effectively maintain the excellent piezoelectric properties and high-power vibration performance of the material, avoiding the problem of material performance degradation during water-based processing. The ceramic obtained after sintering has a high piezoelectric constant ( d 33 =287 pC / N), Mechanical Quality Factor ( Q m =1213) and vibration velocity ( V m With a vibration frequency of 2.3 m / s, it exhibits excellent high-power vibration characteristics, meeting the application requirements of high-power piezoelectric transducers and other devices. This invention realizes the water-based casting fabrication of lead-based high-power piezoelectric ceramics, expanding the application scope of water-based casting technology in the field of high-power piezoelectric ceramics while ensuring high-performance material output, and providing an effective technical solution for the green fabrication of high-reliability piezoelectric ceramic devices. Attached Figure Description

[0018] Figure 1 Viscosity testing of suspensions with different amounts of AKM-0531 dispersant; Figure 2 The results of ion leaching tests on PMnN-PYN-PZT ceramic powder under different pH conditions; Figure 3 The results of the Zeta potential test of PMnN-PYN-PZT suspension after adding AKM-0531 dispersant; Figure 4 (ad) represents the curves showing the apparent viscosity and shear stress of the water-based cast slurry as a function of shear rate. Figure 5 (ad) is the tensile property test curve of water-based cast ceramic thick film; Figure 6 A photograph of the actual product after water-based cast ceramic thick film stacking; Figure 7The TG-DSC thermal analysis curves of water-based cast ceramic thick films in air atmosphere are shown. Figure 8 X-ray diffraction (XRD) patterns of PMnN-PYN-PZT ceramic samples after sintering in an oxygen atmosphere; Figure 9 The image shows the scanning electron microscope (SEM) morphology of the cross-section of the sintered PMnN-PYN-PZT ceramic sample. Figure 10 The impedance and phase angle curves of the PMnN-PYN-PZT ceramic sample after sintering are shown. Figure 11 The results show the vibration velocity test results of the sintered PMnN-PYN-PZT ceramic sample under AC electric field excitation. Detailed Implementation

[0019] To enable those skilled in the art to understand the features and effects of the present invention, the terms and expressions used in the specification and claims are explained and defined in general below. Unless otherwise specified, all technical and scientific terms used herein have the ordinary meaning understood by those skilled in the art regarding the present invention, and in case of conflict, the definitions in this specification shall prevail.

[0020] The theories or mechanisms described and disclosed herein, whether right or wrong, should not in any way limit the scope of the invention, that is, the contents of the invention can be implemented without being limited by any particular theory or mechanism.

[0021] In this document, all features defined by numerical ranges or percentage ranges, such as numerical values, quantities, contents, and concentrations, are for the sake of brevity and convenience only. Accordingly, descriptions of numerical ranges or percentage ranges should be considered as covering and specifically disclosing all possible sub-ranges and individual numerical values ​​(including integers and fractions) within those ranges.

[0022] In this article, unless otherwise specified, “contains,” “includes,” “containing,” “has,” or similar terms cover the meanings of “composed of” and “mainly composed of,” for example, “A contains a” covers the meanings of “A contains a and others” and “A contains only a.”

[0023] For the sake of brevity, not all possible combinations of the technical features in each implementation scheme or embodiment are described herein. Therefore, as long as there is no contradiction in the combination of these technical features, the technical features in each implementation scheme or embodiment can be combined arbitrarily, and all possible combinations should be considered within the scope of this specification.

[0024] The purpose of this invention is to provide a water-based tape casting process for preparing lead-based high-power piezoelectric ceramics. This addresses the problems encountered by existing water-based tape casting technologies, which are primarily used in lead-free piezoelectric ceramic systems, and which suffer from insufficient powder chemical stability, difficulty in controlling slurry dispersion and rheological properties, and difficulty in maintaining high-power performance after sintering in lead-based high-power hard piezoelectric ceramic applications. By optimizing the slurry composition and rheological properties, stable preparation of thick ceramic films is achieved, while maintaining high power performance. d 33 At the same time, it achieves excellent mechanical quality factor ( Q m ) and high-power vibration performance.

[0025] This invention uses 0.06Pb(Mn) 1 / 3 Nb 2 / 3 O3-0.04Pb(Yb) 1 / 2 Nb 1 / 2 Using high-power piezoelectric ceramic powder of O3-0.42PbTiO3-0.48PbZrO3 (PMnN-PYN-PZT) as the research object, deionized water as the solvent, polyether dispersant AKM-0531, polyvinyl alcohol (PVA) as the binder, polyethylene glycol (PEG) as the plasticizer, and Aladdin defoamer 204 as the defoamer, ceramic green bodies with good film-forming properties, flexibility, and uniform microstructure were obtained by optimizing the slurry dispersion state, solid content, and rheological properties. After debinding and sintering, high-power piezoelectric ceramics with excellent comprehensive properties were prepared. d 33 =287, Q m =1213 and high vibration velocity V m =2.3 m / s), its vibration velocity is higher than that of commercial PZT ceramics, showing excellent high-power vibration performance and application prospects.

[0026] This embodiment provides a water-based casting method for preparing lead-based high-power piezoelectric ceramics. Deionized water is used as the dispersion medium in the casting system. The chemical stability of the lead-based piezoelectric ceramic powder in the water-based environment is improved by adjusting the pH value of the slurry. Furthermore, by adding dispersants, binders, plasticizers, and defoamers, a ceramic slurry with good dispersion stability and suitable rheological properties is obtained. After casting, drying, lamination hot pressing, debinding, and sintering, a high-power piezoelectric ceramic with uniform structure and excellent performance is obtained. Step 1: High-power piezoelectric ceramic powders PMnN-PYN-PZT are added to an aqueous solution containing a dispersant, and mixed in a mixer at 1800 r / min for 4 min to achieve uniform dispersion. The dispersant is a polyether dispersant AKM-0531, and its addition amount is 0.2~1.2 wt% of the ceramic powder mass, preferably 0.6 wt%.

[0027] Step 2: Add acetic acid and / or ammonia to the uniformly dispersed ceramic suspension obtained in Step 1 to adjust the pH value of the slurry system to maintain the pH value of the suspension at 8-10, so as to improve the chemical stability of the powder in the water-based environment and improve the dispersion state between particles, preferably 10.

[0028] Step 3: Add binder, plasticizer, and defoamer to the suspension obtained in Step 2, and mix thoroughly using a defoaming mixer at 1800 r / min for 10-15 min to ensure uniform dispersion of all components. The binder is polyvinyl alcohol (PVA), added at 4-7 wt% of the ceramic powder mass, preferably 6 wt%; the plasticizer is polyethylene glycol (PEG), added at 0.75-3 wt% of the ceramic powder mass, preferably 1 wt%; and the defoamer is Aladdin defoamer 204, added at 1.3 wt% of the ceramic powder mass.

[0029] Step 4: Use the slurry obtained in Step 3 as the casting slurry. By adjusting the proportion of organic additives, the slurry has a suitable apparent viscosity and obvious shear thinning characteristics to meet the requirements of spreading, film formation and continuous molding during the casting process.

[0030] Step 5: Add the casting slurry obtained in Step 4 to the casting equipment for casting. The casting doctor blade height is 200~250 μm, the casting speed is 0.15~0.20 m / min, and the drying temperature is 40~70 ℃. The thickness of the cast film is controlled by adjusting the doctor blade height to obtain a ceramic thick film with a thickness of 20~30 μm and a smooth surface.

[0031] Step 6: Cut the ceramic thick film obtained in Step 5 into 25 mm × 25 mm dimensions, stack them according to actual needs, and place them in a warm isostatic pressing (WIP) machine for forming. The forming process includes: preheating at 75 ℃ for 30 min, followed by holding at pressures of 10 MPa, 25 MPa, and 40 MPa for 2 min respectively, to obtain a uniformly structured cast ceramic green body.

[0032] Step 7: Place the cast green body obtained in Step 6 into a sintering furnace for debinding treatment. The debinding temperature range is 30~400 ℃, the heating rate is 0.1~0.5 ℃ / min, and the holding time is 120 min, in order to remove the organic components in the green body.

[0033] Step 8: Place the ceramic blank obtained in Step 7 after debinding into an atmosphere sintering furnace for sintering. The sintering atmosphere is O2, the sintering temperature is 1150 ℃, the heating rate is 1 ℃ / min, and the holding time is 240 min. Finally, multilayer PMnN-PYN-PZT high-power piezoelectric ceramic is obtained.

[0034] In summary, by synergistically controlling the chemical stability of powder, the dispersion state of slurry, and the rheological properties during water-based casting, the risks of selective leaching of elements, insufficient slurry stability, and unstable molding quality during the water-based processing of lead-based high-power piezoelectric ceramics are reduced. The described process is simple, the parameters are easy to control, and it has good repeatability. It can prepare multilayer high-power piezoelectric ceramics of different sizes and structures according to actual application requirements, providing an effective technical solution for the preparation of high-performance high-power piezoelectric ceramics.

[0035] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.

[0036] The following examples use instruments and equipment conventional in the art. Experimental methods in the following examples, unless otherwise specified, are generally performed under conventional conditions or as recommended by the manufacturer. All raw materials used in the following examples are conventional commercially available products with specifications conventional in the art. In this specification and the following examples, unless otherwise specified, "%" refers to weight percentage, "parts" refers to parts by weight, and "ratio" refers to weight proportion.

[0037] Example 1 The PMnN-PYN-PZT multilayer high-power piezoelectric ceramics are prepared using the water-based casting process described in this invention. The specific implementation steps are as follows: PMnN-PYN-PZT ceramic powder was added to deionized water containing polyether dispersant AKM-0531, such as... Figure 1As shown, the viscosity of the suspension decreased significantly with increasing dispersant content. Considering the volatilization of organic matter during subsequent debinding, the preferred dispersant content is 0.6 wt% of the ceramic powder mass. The mixture was then stirred at 1800 r / min for 4 min in a mixer / deaerator to ensure thorough dispersion of the ceramic powder. Based on the results of ion leaching and Zeta potential tests... Figure 2 and Figure 3 As shown, when pH = 10, Pb 2+ Mn 4+ and Ti 4+ The leaching contents of all three ions were minimized, and the absolute value of the Zeta potential reached 40 mV. Based on the test results, ammonia was added to the resulting suspension to adjust the pH of the slurry to 10, in order to improve the chemical stability and dispersion of the powder in an aqueous environment. Subsequently, polyvinyl alcohol (PVA), polyethylene glycol (PEG), and defoamer 204 were added to the obtained suspension, wherein the amounts of PVA, PEG, and defoamer added were 6 wt%, 3 wt%, and 1.3 wt% of the ceramic powder mass, respectively, and the mixture was stirred at 1800 r / min for 10 min to obtain a water-based casting slurry.

[0038] like Figure 4 As shown in (a), the obtained slurry exhibits obvious shear-thinning characteristics, meeting the requirements for slurry flow performance during the casting process. Fitting the test data using Sisko and Herschel-Bulkley methods yields a consistency coefficient of 14.11 Pa. s n The flow index is 0.21 and the yield stress is 11.42 Pa.

[0039] Using this slurry for casting produces ceramic thick films with good flexibility and mechanical strength. For example... Figure 5 As shown in (a), the maximum tensile stress of the cast film reaches 2.3 MPa, and the fracture strain is about 17%.

[0040] Example 2 The PMnN-PYN-PZT multilayer high-power piezoelectric ceramics are prepared using the water-based casting process described in this invention. The specific implementation steps are as follows: PMnN-PYN-PZT ceramic powder was added to deionized water containing polyether dispersant AKM-0531, such as... Figure 1 As shown, the viscosity of the suspension decreased significantly with increasing dispersant content. Considering the volatilization of organic matter during subsequent debinding, the preferred dispersant content is 0.6 wt% of the ceramic powder mass. The mixture was then stirred at 1800 r / min for 4 min in a mixer / deaerator to ensure thorough dispersion of the ceramic powder. Based on the results of ion leaching and Zeta potential tests... Figure 2 and Figure 3 As shown, when pH = 10, Pb 2+ Mn 4+ and Ti 4+ The leaching contents of all three ions were minimized, and the absolute value of the Zeta potential reached 40 mV. Based on the test results, ammonia was added to the resulting suspension to adjust the pH of the slurry to 10, in order to improve the chemical stability and dispersion of the powder in an aqueous environment.

[0041] Subsequently, polyvinyl alcohol (PVA), polyethylene glycol (PEG), and defoamer 204 were added to the obtained suspension, wherein the amounts of PVA, PEG, and defoamer added were 6 wt%, 1.5 wt%, and 1.3 wt% of the ceramic powder mass, respectively, and the mixture was stirred at 1800 r / min for 10 min to obtain a water-based casting slurry.

[0042] like Figure 4 As shown in (b), the obtained slurry exhibits obvious shear-thinning characteristics, meeting the requirements for slurry flow performance during the casting process. Fitting the test data using Sisko and Herschel-Bulkley methods yields a consistency coefficient of 14.88 Pa. s n The flow index is 0.22 and the yield stress is 8.92 Pa.

[0043] Using this slurry for casting produces ceramic thick films with good flexibility and mechanical strength. For example... Figure 5 As shown in (b), the maximum tensile stress of the cast film reaches 3.0 MPa, and the fracture strain is about 12%.

[0044] Example 3 The PMnN-PYN-PZT multilayer high-power piezoelectric ceramics are prepared using the water-based casting process described in this invention. The specific implementation steps are as follows: PMnN-PYN-PZT ceramic powder was added to deionized water containing polyether dispersant AKM-0531, such as... Figure 1 As shown, the viscosity of the suspension decreased significantly with increasing dispersant content. Considering the volatilization of organic matter during subsequent debinding, the preferred dispersant content is 0.6 wt% of the ceramic powder mass. The mixture was then stirred at 1800 r / min for 4 min in a mixer / deaerator to ensure thorough dispersion of the ceramic powder. Based on the results of ion leaching and Zeta potential tests... Figure 2 and Figure 3 As shown, when pH = 10, Pb 2+ Mn 4+ and Ti 4+The leaching contents of all three ions were minimized, and the absolute value of the Zeta potential reached 40 mV. Based on the test results, ammonia was added to the resulting suspension to adjust the pH of the slurry to 10, in order to improve the chemical stability and dispersion of the powder in an aqueous environment.

[0045] Subsequently, polyvinyl alcohol (PVA), polyethylene glycol (PEG), and defoamer 204 were added to the obtained suspension, wherein the amounts of PVA, PEG, and defoamer added were 6 wt%, 1 wt%, and 1.3 wt% of the ceramic powder mass, respectively, and the mixture was stirred at 1800 r / min for 10 min to obtain a water-based casting slurry.

[0046] like Figure 4 As shown in (c), the obtained slurry exhibits obvious shear-thinning characteristics, meeting the requirements for slurry flow performance during the casting process. Fitting the test data using Sisko and Herschel-Bulkley methods yields a consistency coefficient of 16.36 Pa. s n The flow index is 0.23 and the yield stress is 7.20 Pa.

[0047] Using this slurry for casting produces ceramic thick films with good flexibility and mechanical strength. For example... Figure 5 As shown in (c), the maximum tensile stress of the cast film reaches 3.3 MPa, and the fracture strain is about 18%. The cast film obtained in the embodiment has the highest tensile stress and fracture strain.

[0048] Example 4 The PMnN-PYN-PZT multilayer high-power piezoelectric ceramics are prepared using the water-based casting process described in this invention. The specific implementation steps are as follows: PMnN-PYN-PZT ceramic powder was added to deionized water containing polyether dispersant AKM-0531, such as... Figure 1 As shown, the viscosity of the suspension decreased significantly with increasing dispersant content. Considering the volatilization of organic matter during subsequent debinding, the preferred dispersant content is 0.6 wt% of the ceramic powder mass. The mixture was then stirred at 1800 r / min for 4 min in a mixer / deaerator to ensure thorough dispersion of the ceramic powder. Based on the results of ion leaching and Zeta potential tests... Figure 2 and Figure 3 As shown, when pH = 10, Pb 2+ , Mn 4+ , and Ti 4+The leaching contents of all three ions were minimized, and the absolute value of the Zeta potential reached 40 mV. Based on the test results, ammonia was added to the resulting suspension to adjust the pH of the slurry to 10, in order to improve the chemical stability and dispersion of the powder in an aqueous environment.

[0049] Subsequently, polyvinyl alcohol (PVA), polyethylene glycol (PEG), and defoamer 204 were added to the obtained suspension, wherein the amounts of PVA, PEG, and defoamer added were 6 wt%, 0.75 wt%, and 1.3 wt% of the ceramic powder mass, respectively, and the mixture was stirred at 1800 r / min for 10 min to obtain a water-based casting slurry.

[0050] like Figure 4 As shown in (d), the obtained slurry exhibits obvious shear-thinning characteristics, meeting the requirements for slurry flow performance during the casting process. Fitting the test data using Sisko and Herschel-Bulkley methods yields a consistency coefficient of 22.51 Pa. s n The flow index is 0.25 and the yield stress is 7.05 Pa.

[0051] Using this slurry for casting produces ceramic thick films with good flexibility and mechanical strength. For example... Figure 5 As shown in (d), the maximum tensile stress of the cast film reached 2.6 MPa, and the fracture strain was approximately 3.25%. Example 5 Based on the rheological behavior and mechanical property test results of the above embodiments, the formulation of Example 3 was selected to successfully prepare a water-based cast lead-based piezoelectric ceramic thick film with both sufficient strength and flexibility; subsequently, the green tape was cut, warm isostatically pressed and debinded and sintered.

[0052] The obtained cast film was cut and stacked, then placed in a warm isostatic pressing (WIP) apparatus for forming. The forming process included: preheating at 75 ℃ for 120 min, followed by holding at pressures of 10 MPa, 25 MPa, and 40 MPa for 2 min respectively, to obtain cast ceramic preforms. Figure 6 As shown, the resulting green blank has a smooth surface and uniform structure, exhibiting good molding quality.

[0053] The resulting cast green body is then subjected to debinding and sintering treatment. First, as... Figure 7 The cast green blank is placed in a sintering furnace for debinding. The debinding temperature range is 30~400 ℃, the heating rate is 0.1~0.5 ℃ / min, the holding time is 120 min, and then it is cooled in the furnace.

[0054] The debinding sample was placed in an oxygen atmosphere furnace for sintering at a temperature of 1150 ℃, a heating rate of 1 ℃ / min, and a holding time of 240 min, finally obtaining a PMnN-PYN-PZT multilayer high-power piezoelectric ceramic sample.

[0055] The phase composition of the obtained ceramic sample is as follows Figure 8 As shown, XRD results indicate that the sample exhibits a single perovskite structure with no obvious impurity phase formation.

[0056] Sample microstructure such as Figure 9 As shown, the ceramic has a dense internal structure with uniform grain distribution and a density of approximately 99%. The piezoelectric constant... d 33 The value was 287, and the electrical and high-power performance of the sample was further tested.

[0057] like Figure 10 As shown, impedance analysis results indicate that the obtained ceramic has a high mechanical quality factor. Q m The vibration velocity of the sample reached 1213. Figure 11 As shown, the maximum vibration velocity of the sample under an AC electric field excitation of 100 V / mm is... V m It reaches 2.3 m / s, demonstrating good high-power performance.

[0058] The above content is only for illustrating the technical concept of the present invention and should not be construed as limiting the scope of protection of the present invention. Any modifications made to the technical solution based on the technical concept proposed in this invention shall fall within the scope of protection of this invention.

Claims

1. A method for preparing lead-based high-power piezoelectric ceramics using water-based casting molding, characterized in that, Includes the following steps: S1, lead-based high-power piezoelectric ceramic powder is added to an aqueous solution containing a dispersant to form a suspension; the dispersant is a polyether dispersant AKM-0531, and its addition amount is 0.2~1.2 wt% of the mass of the lead-based high-power piezoelectric ceramic powder. S2, add an acid-base regulator to the suspension obtained in S1 to adjust the pH of the suspension to 8-10; S3, add a binder, plasticizer, and defoamer to the suspension obtained in S2 to obtain a water-based casting slurry, wherein the binder is polyvinyl alcohol, added at 4-7 wt% of the lead-based high-power piezoelectric ceramic powder; the plasticizer is polyethylene glycol, added at 0.75-3 wt% of the lead-based high-power piezoelectric ceramic powder; and the defoamer is defoamer 204, added at 1.3 wt% of the lead-based high-power piezoelectric ceramic powder. S4, the water-based casting slurry obtained in S3 is cast into a film in a casting machine to obtain a cast film; S5, the cast film obtained in S4 is laminated and isostatically pressed to obtain a cast film preform; S6. The cast film preform obtained in S5 is subjected to debinding treatment and then sintered in an oxygen atmosphere to obtain lead-based high-power piezoelectric ceramic.

2. The water-based casting molding preparation method according to claim 1, characterized in that, In S1, the chemical composition of the lead-based high-power piezoelectric ceramic powder is 0.06Pb(Mn) 1 / 3 Nb 2 / 3 O3-0.04Pb(Yb) 1 / 2 Nb 1 / 2 O3-0.42PbTiO3-0.48PbZrO3; The lead-based high-power piezoelectric ceramic powder has an average particle size of 200~300 nm.

3. The water-based casting molding preparation method according to claim 1, characterized in that, In S2, the acid-base regulator is acetic acid and / or ammonia.

4. The water-based casting molding preparation method according to claim 1, characterized in that, In S3, the amount of polyvinyl alcohol added is 6 wt% of the mass of lead-based high-power piezoelectric ceramic powder, and the amount of polyethylene glycol added is 1 wt% of the mass of lead-based high-power piezoelectric ceramic powder.

5. The water-based casting molding preparation method according to claim 1, characterized in that, In S4, the doctor blade height is controlled at 200~250 μm, the casting rate is 0.15~0.20 m / min, and the drying temperature is 40~70 ℃.

6. The water-based casting molding preparation method according to claim 1, characterized in that, In S4, the thickness of the cast film is 20~30 μm.

7. The water-based casting molding preparation method according to claim 1, characterized in that, In S5, the warm isostatic pressing includes: preheating at 75 °C for 120 min, and then holding at pressures of 10 MPa, 25 MPa and 40 MPa for 2 min each.

8. The water-based casting molding preparation method according to claim 1, characterized in that, In S6, the heating range of the glue removal process is 30~400 ℃, the heating rate is 0.1~0.5 ℃ / min, and the holding time is 120 min.

9. The water-based casting molding preparation method according to claim 1, characterized in that, In S6, the sintering temperature is 1150 ℃ and the holding time is 240 min.

10. A lead-based high-power piezoelectric ceramic prepared by the method according to any one of claims 1 to 9, characterized in that, piezoelectric constant d 33 ≥287, Mechanical Quality Factor Q m ≥ 1200, vibration velocity V m ≥ 2.0 m / s.

Citation Information

Patent Citations

  • Water-based tape casting method for lead-free piezoelectric ceramic film

    CN121779114A